Investigation of the Change in Antibody Levels of COVID-19 RT-PCR Positive Patients Over Time - Çöplü, Nilay; Kılınç, Çetin; Özbek, Rıdvan; Demir, Celal; Çalışır, Büşra; Aygün, Zeynep (Bilimsel Tip Publishing House, 2023)
Introduction: Our aim was to determine the change in antibody response against COVID-19 over time and estimate the duration required for it to decrease to the threshold of the ELISA test in patients with a positive COVID-19 RT-PCR test. The purpose was to present data for epidemiological measures related to the risk of reinfection or the need for booster doses of the vaccine.Materials and Methods: The real-time RT-PCR method was used for diagnosing patients. Serum samples were collected from 177 patients 2-60 days after their COVID-19 RT-PCR test, and a second serum was taken from 35 patients from the first group 94-139 days after the initial sampling. A total of 212 serum samples were included in the study, and the Euroimmun ELISA (Lubeck, Germany) assay was used. Statistical analyses were performed using IBM SPSS Statistics software (version 22.0, IBM Corporation, Chicago, IL) for Windows.Results: The estimated time taken for antibodies to reach the threshold value varied according to immunoglobulin classes, targeted antigen, and disease severity. The longest durations were detected in the group that provided two serum samples, for anti-S IgG antibodies, and for patients with a severe clinical course. In the overall group, the durations were 62, 129, 72, and 41 days after the PCR test for anti-S IgG, anti-NCP IgG, and anti-NCP IgM, respectively. In the group that provided two serum samples, the durations were 197, 252, and 218 days for the same antibodies, respectively. Additionally, it was observed that even the first serum samples were below the threshold values for anti-NCP IgM. In terms of the clinical course, the longest durations were observed in patients with severe illness: 70, 158, 83, and 45 days for the aforementioned immunoglobulins, respectively. Additionally, 32% of patients did not have detectable antibodies.Conclusion: These results indicate that humoral immunity, as measured by anti-S IgG which has the longest duration and is most compatible with protective neutralizing antibodies, may remain protective for over four months and even up to eight months.
Keywords: 3. Good health